Control of long-term deflections of RC beams using reinforcements and low-shrinkage concrete. Issue 2 (30th March 2020) - Sousa, Helder; Mitoulis, Stergios A.; Psarras, Konstantinos; Tegos, Ioannis A.
Abstract : An experimentally based programme was conducted to assess the influence of heterogeneity on the long-term deflection of reinforced concrete (RC) elements with compression reinforcement and low-shrinkage concrete. These two structural measures are usually employed by designers to mitigate deflection of concrete beams, slabs and bridge decks due to creep and shrinkage effects. Control of creep and shrinkage deflections is important for successful design of concrete elements as the deflections influence their sizing and thus the associated costs. A 5 year experimental study was undertaken to address the most common alternative design approaches to alleviate long-term deflections of concrete. These included variable reinforcement ratios within the compressive zone, variable tensile reinforcement ratios, low-shrinkage concrete within the compressive zone and a combination of these measures. In total, 12 cantilever beam specimens were tested in the laboratory under controlled environmental conditions, supported by a time-dependent finite-element model. Both numerical and experimental results showed RC beam deflection reductions of up to 85% could be achieved when both compressive reinforcement and low-shrinkage concrete were employed.